Promotion of human rights by providing equal employment opportunities for the disadvantaged workers in ASEAN - Furuokaa, Fumitaka; Lim, Beatrice; Pazim, Khairul Hanim (AEI Insights, 2021)
The promotion and protection of human rights is a key political principle of ASEAN and the ASEAN member states have made efforts to safeguard human rights and freedom of all ASEAN citizens, including the disadvantaged workers. This paper examines the ASEAN countries’ commitment and labour policy to promote equal employment opportunities for women, the elderly and persons with disabilities. The findings of this study would provide better insights to the issues of human rights in the labour market among ASEAN countries. It can serve as a resource for researchers, practitioners and policymakers for policymaking in ensuring that disadvantaged workers are not excluded from being able to fully enjoy their right to work as their participation in the labour market could in turn be one of the solutions to reduce high unemployment rate suffered in some ASEAN countries.